Effects of Antenatal Betamethasone on Fetal Doppler Indices and Short Term Fetal Heart Rate Variation in Early Growth Restricted Fetuses - Fratelli, Nicola; Prefumo, Federico; Wolf, Hans; Hecher, Kurt; Visser, Gerard H. A.; Giussani, Dino; Derks, Jan B.; Shaw, Caroline J.; Frusca, Tiziana; Ghi, Tullio; Ferrazzi, E.; Lees, Christoph C.; on behalf of the TRUFFLE Group; TRUFFLE Group authors; Arabin, B.; Bilardo, C. M.; Brezinka, C.; Diemert, A.; Duvekot, J. J.; Ganzevoort, W.; Marlow, N.; Martinelli, P.; Ostermayer, E.; Papageorghiou, A. T.; Schlembach, D.; Schneider, K. T. M.; Thilaganathan, B.; Thornton, J.; Todros, T.; Valcamonico, A.; van Wassenaer-Leemhuis, A.; TRUFFLE Group collaborating authors; Aktas, A.; Borgione, S.; Chaoui, R.; Cornette, J. M. J.; Diehl, T.; van Eyck, J.; van Haastert, I. C.; Lobmaier, S.; Lopriore, E.; Missfelder-Lobos, H.; Mansi, G.; Martelli, P.; Maso, G.; Maurer-Fellbaum, U.; Mensing van Charante, N.; Mulderde Tollenaer, S.; Napolitano, R.; Oberto, M.; Oepkes, D.; Oggé, G.; van der Post, J. A. M.; Preston, L.; Raimondi, F.; Reiss, I. K. M.; Scheepers, L. S.; Skabar, A.; Spaanderman, M.; Weisglas-Kuperus, N.; Zimmermann, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To investigate the effects of the antenatal administration of betamethasone on fetal Doppler and short term fetal heart rate variation (CTG-STV) in early growth restricted (FGR) fetuses.Materials and Methods Post hoc analysis of data derived from the TRUFFLE study, a prospective, multicenter, randomized management trial of severe early onset FGR. Repeat Doppler and CTG-STV measurements between the last recording within 48 hours before the first dose of betamethasone (baseline value) and for 10 days after were evaluated. Multilevel analysis was performed to analyze the longitudinal course of the umbilico-cerebral ratio (UC ratio), the ductus venosus pulsatility index (DVPIV) and CTG-STV.Results We included 115 fetuses. A significant increase from baseline in CTG-STV was found on day + 1 (p = 0.019) but no difference thereafter. The DVPIV was not significantly different from baseline in any of the 10 days following the first dose of betamethasone (p = 0.167). Multilevel analysis revealed that, over 10 days, the time elapsed from antenatal administration of betamethasone was significantly associated with a decrease in CTG-STV (p = 0.045) and an increase in the DVPIV (p = 0.001) and UC ratio (p < 0.001).Conclusion Although steroid administration in early FGR has a minimal effect on increasing CTG-STV one day afterwards, the effects on Doppler parameters were extremely slight with regression coefficients of small magnitude suggesting no clinical significance, and were most likely related to the deterioration with time in FGR. Hence, arterial and venous Doppler assessment of fetal health remains informative following antenatal steroid administration to accelerate fetal lung maturation.
Keywords: fetal growth restriction; betamethasone; obstetrics